Geometry Literacy Test to Explore Creative Thinking Behavior of Visually Impaired Students: A Research and Development Study - Panglipur, Indah Rahayu; B. Enad, Fernando; Rita Fiantika, Feny (Indonesian Educational Research Journal, 2026)
This study was motivated by the limited availability of assessment instruments designed to explore creative thinking behavior among visually impaired students in geometry learning. The study aimed to develop a geometry literacy test consisting of problem items, companion guides, and alternative behavioral rubrics to examine students’ creative thinking behavior. The research subjects included seven visually impaired students, comprising three blind students and four students with low vision, selected based on their ability to communicate effectively and understand mathematical instructions. The development process employed a 4D instructional development model involving expert validation and limited trials to evaluate the effectiveness of the instrument. Validation results showed average scores of 3.82 for the test items, 3.85 for the companion guide, and 3.88 for the alternative rubric out of a maximum score of 4, indicating high validity. Trial findings revealed observable creative thinking behaviors across fluency, flexibility, elaboration, and originality aspects. Identified behaviors included expressing, describing, tactile exploration, composing, reasoning, demonstrating, manipulating, and synthesizing ideas. The developed geometry literacy test is valid and effective for exploring creative thinking behavior among visually impaired students within inclusive mathematics learning contexts.